The Effect Of Audit Delay, Debt Default, And Opinion Shopping On Receiving Going Concern Audit Opinions - Maghriby, Bimbim; Almirah, Sahda (Review of Accounting and Business, 2022)
Intense competition makes the need for financial reports to be adequate and accountable for those who need financial report information. The world of capital markets makes investors have a tool to measure the performance of financial conditions through financial reports to view information in the form of financial performance, cash flow and financial position to be used in making investment decisions. Financial reports are able to inform whether a company has a going concern. The method in this study uses secondary data through data acquisition from Mining Sector Companies on the Indonesia Stock Exchange (IDX). The output of this research is a published journal and is expected to be input for further research